Risk predictor for ma/aria in pregnancy and the role of chloroquine in /ow endemic area - Iwan Dwiprahasto, Iwan Dwiprahasto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2004)
Background: Pregnant women in malaria-endemic areas are uniquely susceptible to infection with Plasmodium falciparum and this susceptibility is greatest during first pregnancies. Malaria causes serious complications in pregnant women, especially in those who have a low level of acquired immunity before pregnancy.Objective: to assess the risk predictors for malaria during pregnancy and the role of chloroquine in low endemic area of malaria in Jepara districtDesign: A longitudinal study of all pregnant mother was carried out in Batealit and Mayong I subdistricts of Jepara district between June 1997-August 1999. All pregnant women were screened for peripheral parasitaemia through active surveillance. Women who had parasitaemia were treated with chloroquine for 3 days. Blood smears were then examined on days 4, 7, 14 and 21 after completion of the chloroquine course. All women irrespective of the blood smear results at enrolment were followed up once every two weeks until delivery.Results: Among 3099 pregnant women enrolled in the study, only 58 women had malaria infection, giving an incidence rate of 1.9/100 pregnant women. In this study low income is a significant risk predictor for malaria (OR= 11.03; 95%Cl: 3.91-31.08). Women who had reported a history of malaria or history of taking antimalarial drugs 6 months before their last menstrual period (LMP) showed an increased risk of developing malaria during pregnancy (OR= 10.56; 95%Cl: 4.57-23.72 and OR = 10.90; 95%Cl: 4.4825.61) respectively. Among those infected by P.falciparum and P. vivax and treated with chloroquine, complete parasite clearance was found in day 7.Conclusions: This study shows that low income, history of malaria within 6 months before LMP and history of taking antimalarial drugs within 6 months before LMP are best predictor for malaria in pregnancy in low endemic area. This study also shows that chloroquine is still effective for treating malaria falciparum in pregnancy in Batealit and Mayong I subdistricts, JeparaKeyword: malaria - pregnancy - low endemic area - risk-predictor - chloroquine